Law Enforcement in The Investigation of Criminal Acts of Destruction of Evidence - Muh Malikul Mulki Nur; M. Syukri Akub; Hijriah Adhyanti Mirzana (PT Mattawang Mediatama Solution, 2022)
This study aims to analyze law enforcement in the investigation of criminal acts of destruction of evidence in the jurisdiction of Kendari City and the role of evidence in court trials if the confiscated proof cannot be shown because it has been destroyed due to demonstrations and legal efforts by police officers in the Prevention of Destruction of Evidence Due to Demonstrations in Kendari City. This research is an empirical research type. Collecting data is through field studies, literature studies, interviews, and library materials relevant to this research. Furthermore, the data obtained were analyzed qualitatively and presented descriptively following explanations closely related to this research. A conclusion was drawn based on the analysis carried out. The study results indicate that law enforcement in the investigation of criminal acts of destruction of evidence is a form of accountability for the Kendari City Police Police; the police carry out the law enforcement process following their authority and the court.